The role of local government in the empowerment of MSME actors in Palopo City - Rahmayanti, Alvira (Department of Government Science, 2024)
The micro, small, and medium enterprise (MSME) activities cover almost all business fields, and the existence of MSMEs is crucial, especially for increasing income for low-income groups. This study aims to find out how the government carries out its role as a facilitator, as a regulator, and as a catalyst on the eight indicators based on the Regional Regulations of Palopo City, especially in the development of MSMEs in Palopo City. The research type is qualitative research, which explains events that actually occurred in the field during the study. Informants were heads of cooperatives and MSMEs, heads of the UMKM sector, staff of the cooperatives and MSMEs office of Palopo City, and several MSME business actors. Data collection was carried out through direct field observations, interviews, and documentation with informants. The findings indicate that the government's role in empowering MSMEs was carried out by the Office of Cooperatives and MSMEs, and the government carried out its role as a facilitator, a regulator, and a catalyst. The government has a major influence in carrying out the empowerment, and it can help MSME actors maintain and improve their business by providing access to financing and capital, promotion, coaching, mentoring training, and growing the business climate. Finally, we will look at the condition of MSMEs, especially micro-type businesses that have grown densely in various areas in Palopo City.